â€œDIFFERENTIATED INSTRUCTIONâ€: SOLUSI PEMBELAJARAN DALAM KEBERAGAMAN SISWA DI KELAS INKLUSIF - Dinar Westri Andini (Universitas Sarjanawiyata Tamansiswa, 2016)
Education must be able to accommodate towards to all those differences, and must provide all the students need as well encouraging them to actively participate in the learning process. The teaching process in class is still not giving the best support towards each studentâ€™s need. Most teachers still have a mindset that all students must have the same ability and has no clue how to probe the students need. The teaching process thatâ€™s been given are usually seem monotone and still using the teacher centered procedure, this procedure will hampering the critical thinking of students. I will share about the implementation from one of learning model which is differentiating instruction. This model can accommodate diversity students based on different readiness levels, interests and learning profile.